Structural bioinformatics tools for drug design : extraction of biologically relevant information from structural databases /: extraction of biologically relevant information from structural databases. ([2016]) - Koča, Jaroslav; Vařeková, Radka Svobodová; Pravda, Lukáš; Berka, Karel; Geidl, Stanislav; Sehnal, David; Otyepka, Michal
No abstract available